Comparative study on structural modification of Ceiba pentandra for oil sorption and palm oil mill effluent treatment - Abdullah, M.A. (Bellwether Publishing, Ltd., 2015)
Abstract: The performance of raw Ceiba pentandra (L.) Gaertn (raw kapok fibers (RKF)) for oil sorption and palm oil mill effluent (POME) treatment was compared with structurally modified kapok (NaOH-treated (SKF) and surface-modified kapok fiber (SMKF)) and bentonite clay. Based on FTIR, kapok wax functional group at 1726/cm was not detected in SKF rendering higher hydrophilicity. The reduction in peak intensity at 473 and 523/cm upon HCl treatment of bentonite, suggests the cleavage of SiâOâAl bond layer and SiâOâMg (Fe) bonds. For filtration under gravity at 0.08 g/cm3, SKF showed high POME sorption of 82 g/g, but lower diesel sorption of 23 g/g. With HCl-treated bentonite, POME sorption at 69 g/g was only slightly higher than diesel sorption of 60 g/g. However, RKF and raw bentonite achieved higher removal efficiency of biological oxygen demand, chemical oxygen demand (COD), total organic carbon, and total nitrogen at 74â98 and 72â94, respectively, than with SKF at 66â80, and HCl-treated bentonite at 64â80. In batch mode, SMKF at 0.08 g/cm3 showed the highest oil sorption capacity of 56.7 g/g for Crude Palm Oil (CPO) and 33.7 g/g for diesel. Under continuous mode with 4000 mg/l CPO in water, 99 of COD removal was achieved at all packing densities and flow rates, regardless of kapok packing material. The dynamic oil retention was 96â99 for CPO and 99â100 for diesel at all packing densities. RKF and SMKF can both be suitable sorbent materials for CPO and diesel sorption, and for POME treatment. Â© 2014 Balaban Desalination Publications. All rights reserved.